Crystal structure of diaquabis(ethylenediamine-κ2N,N′)copper(II) bis(p-chlorobenzoate), [Cu(C2H8N2)2(H2O)2](C7H4ClO2)2 - Lee J.-C.; Takahashi H.; Matsui Y. (Zeitschrift für Kristallographie - New Crystal Structures, 2005)
C18H28Cl2CuN4O6, orthorhombic, Pbca (no. 61), a = 10.623(3) Å, b = 7.187(3) Å, c = 29.912(8) Å, V = 2283.7 Å3, Z = 4, Rgt(F) = 0.024, wRref(F) = 0.028, T = 173 K.